Yellow fever surveillance suggests zoonotic and anthroponotic emergent potential - Aliaga-Samanez, Alisa; Real-Giménez, Raimundo; Segura, Marina; Marfil-Daza, Carlos; Olivero-Anarte, Jesús (Nature, 2022)
Yellow fever is transmitted by mosquitoes among human and non-human primates. In the last decades, infections are occurring in areas that had been free from yellow fever for decades, probably as a consequence of the rapid spread of mosquito vectors, and of the virus evolutionary dynamic in which non-human primates are involved. This research is a pathogeographic assessment of where enzootic cycles, based on primate assemblages, could be amplifying the risk of yellow fever infections, in the context of spatial changes shown by the disease since the late 20th century. In South America, the most relevant spread of disease cases affects parts of the Amazon basin and a wide area of southern Brazil, where forest fragmentation could be activating enzootic cycles next to urban areas. In Africa, yellow fever transmission is apparently spreading from the west of the continent, and primates could be contributing to this in savannas around rainforests. Our results are useful for identifying new areas that should be prioritised for vaccination, and suggest the need of deep yellow fever surveillance in primates of South America and Africa.
Keywords: Zoonosis; Patogeografía; Biogeografía; Enfermedades zoonóticas; One health